The transgender-specific intimate partner violence scale for research and practice: Validation in a sample of transgender women. (December 2021) - Peitzmeier, Sarah M.; Wirtz, Andrea L.; Humes, Elizabeth; Hughto, Jaclyn M.W.; Cooney, Erin; Reisner, Sari L.; ,
Abstract: Study/research objective: To develop and validate a brief intimate partner violence (IPV) scale that screens for controlling behaviors and psychological abuse tactics directed toward transgender individuals. Rationale: Transgender individuals are at elevated risk of physical and sexual IPV compared to cisgender individuals. IPV often takes on unique dimensions against transgender individuals, such as when an abusive partner threatens to "out" the transgender person, or use other tactics that weaponize transphobia within the relationship. Standard IPV screeners do not assess this type of transgender-specific IPV (T-IPV). Methods: Between March 2018 and October 2019, a T-IPV scale was tested in two samples (in-person and online) of transfeminine adults (i.e. assigned a male sex at birth and identify with femininity) from the eastern and southern U.S. Exploratory factor analysis (EFA) was conducted with the in-person sample ( N  = 661) to assess construct validity. Confirmatory factor analysis (CFA) was then used in an independent online sample ( N  = 481). Using the combined sample ( N  = 1137), convergent validity was assessed using correlations with other forms of victimization. Multivariable regression models were fit to estimate the relationship between T-IPV and health outcomes. Results: Factor analyses yielded an 8-item unidimensional scale with moderate to good fit. Nearly half the sample (48.7%) experienced at least one scale item. Internal consistency reliability was strong (KR-20 = 0.827). Significant correlations with other forms of victimization indicated convergent validity. Lifetime T-IPV was significantly associated with psychological distress (adjusted prevalence ratio [aPR] = 1.32, 95% CI = 1.13, 1.53), PTSD (aPR = 1.50, 95%CI = 1.31, 1.72), alcohol abuse (aPR = 1.21, 95%CI = 1.01, 1.44), and drug use disorder (aPR = 1.30, 95%CI = 1.06, 2.59). Conclusions: This T-IPV scale is a reliable and unidimensional measure with strong construct validity. T-IPV is independently associated with mental health burden and substance use. Service providers working with transgender clients should screen for T-IPV to avoid missing cases of IPV, and refer to violence response services. Highlights: Transgender people are at elevated risk of intimate partner violence (IPV). IPV can take on trans-specific dimensions, e.g. the abuser threatening to out a partner. We developed an 8-item scale to screen for trans-specific IPV (T-IPV). Our scale shows strong reliability and construct validity. Our scale can be used to screen and refer trans individuals for IPV services.